PENDIDIKAN KESEHATAN SISWA SISWI MAN 4 BANTUL DALAM MENSIKAPI BAHAYA PERGAULAN BEBAS - Endang Khoirunnisa, Endang; Pratiwi, Kurniasari (ABDIMAS Madani, 2023)
Adolescence is a period known as "storm and stress", which is a period filled with conflict. Adolescents or adolescents experience emotional changes and social changes. Adolescence usually occurs about two years after puberty, reflecting the impact of physical changes and deep emotional experiences. According to a survey conducted by the Indonesian Child Protection Committee (KPAI) in 2010, as many as 32% of adolescents aged 14-18 years in big cities in Indonesia have had sexual intercourse. The purpose of this activity is to prepare young people who are against promiscuity and free sex. This activity was held at Madrasah Aliyah Negeri 4 Bantul, Banguntapan District, Bantul Regency on Wednesday 12 December 2018 at 09.00-12.00 WIB. The target of the activity was 44 students of class IX MAN 4 Bantul. This service method is carried out through two stages, each lasting 120 minutes. Before the event begins, a bridging is carried out with the Principal, BK teachers and students who help provide counseling. After all were ready, the students who helped then arranged the sitting positions of the students and circulated attendance and filled out the minutes of counseling. After all participants were present, the event began with the Principal's remarks and prayer readings. Furthermore, after the opening ceremony was completed, the main event was continued, namely counseling activities about health education for students of MAN 4 Bantul in responding to the dangers of promiscuity. The evaluation instrument was in the form of a closed-ended questionnaire consisting of 10 items. The results of the activity Community service outreach activities about health education for students of MAN 4 Bantul in responding to the dangers of promiscuity run smoothly and successfully. Because the concept of the activity is packaged through games, the student participants are very interested in enjoying the activity. Participants, especially female students, did not feel that they were being given material or counseling, because the material was tucked in between games and discussions after the video was played. The enthusiasm of the participants was very good. At the end of the session there was a question and answer session, lots of questions from them about promiscuity, a message from the principal that this activity could be carried out every month with an allotted time of 120 minutes and we agreed and it will be continued by D III students STIKes Akbidyo Midwife This activity is very helpful for teenagers in understanding the dangers of promiscuity and free sex